Pengaruh Program Latihan Rehabilitasi Menggunakan Pijat Refleksi terhadap Nyeri Punggung Bawah - Sinan Husham Rasheed; Saja Khalid Jassim (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. Therapeutic exercise is identified as one of the main rehabilitative approaches that returns the body to its original state, normal, functional and physiological equilibrium and minimizes pain. As a modern scientific field Reflexology by restorative analytic sessions in the pain conditions such as the back pain. massage has proven itself both in health and clinical treatment for corresponding body parts reflex and also has showed effectiveness Hence, the purpose of the current study was to improve lumbar spine rehabilitation as well as the reduction of lower back pain by sampling a number of women aged 50–60 years from Al-Salam Center for Therapy and Rehabilitation. The participants were examined with pre-test for both groups, after the six-weeks rehabilitation program performed, consisted of therapeutic exercises and reflexology massage. Post-test evaluations were conducted at the end of the program to assess the effects of the intervention. Materials and Methods. The research method was experimental in design and a single-group pre-test/post-test. The research consisted of a muscular strength test conducted with a force sensor, the Kinova software in the analysis of the ROM angles, and a pain assessment form used in the evaluation of the pain felt by the participants. A purposive sampling method was used in the selection of six female participants aged 50-60 years from the total eight. The data collection was analyzed in the Statistical Package for the Social Sciences (SPSS) in a comparison of the pre-test and post-test. Results. The findings showed statistically significant differences in pre- and post-tests across the measured variables. These findings indicate a significant enhancement in the strength of the spinal muscles, an increase in range of motion (ROM), and a reduction in lower back pain among the participants. Conclusions. Results show that the implemented rehabilitation program helps to increase spinal muscle strength, flexibility, and pain intensity in patients with low back pain.